Anemia and Its Associated Factors Among Pregnant Women in Babylon Governorate - Iraq (Journal of Pharmaceutical Negative Results, 2022)
Background: The World Health Organization had defined anemia during pregnancy as the hemoglobin concentration of less than 11g\dl, anemia is the commonest disorder in pregnancy and had serious devastating health effects on pregnant women and her fetus and or neonate . Objectives: To find out the relationship of anemia during pregnancy and some associated independent variables(factors). Methodology: A cross sectional study was conducted in Babylon maternity teaching hospital during the period December 20th 2020— through the end of February 2021,the convenient (purposive) sample included (100)pregnant women who were diagnosed as maternal anemia during pregnancy according to WHO guideline and accepted to participate in this study .Data were collected using pretested structured questionnaire . Results: The demographic characteristics that associated with anemia significantly were age (20-29)years which constituted (76%) , intermediate level of education and below which constituted (71%) of the sample . Multigravida. Frequent abortions, previous history of anemia and stillbirths were significantly high among the study sample p< 0.05 .Conclusion: The main associated factors of anemia during pregnancy were : multiple pregnancy , frequent abortions stillbirth, previous history of anemia and other demographic factors such as age, and low level of education , recommended educational programs to pregnant women and health care providers with improvement of Antenatal , natal and postnatal care services are strongly requested .